Bis-imidazolium based poly(phenylene oxide) anion exchange membranes for fuel cells: the effect of cross-linking. Issue 21 (15th May 2019) - Lin, Bencai; Xu, Fei; Chu, Fuqiang; Ren, Yurong; Ding, Jianning; Yan, Feng
Abstract : Cross-linked membranes showed vastly improved alkaline stability, oxidation stability and mechanical properties compared with uncross-linked membranes due to the effective cross-linked structure. Abstract : In the present work, a series of poly(phenylene oxide) (PPO) based uncross-linked and cross-linked anion exchange membranes (AEMs) with bis-imidazolium cations were synthesized and characterized. Compared with cross-linked AEMs, uncross-linked membranes with similar ion exchange capacities showed a much higher water uptake and swelling degree. Cross-linked membranes showed vastly improved alkaline stability, oxidation stability and mechanical properties compared with uncross-linked membranes due to the effective cross-linked structure, and a well-developed hydrophilic/hydrophobic phase separated morphology was observed for cross-linked membranes by atomic force microscopy (AFM). A single cell with a cross-linked membrane (Cross-Im-PPO-75) showed a maximum power density of 212.45 mW cm −2 . Considering the enhanced alkaline stability and mechanical properties, the cross-linked PPO membranes with bis-imidazolium cations are promising AEM materials for alkaline exchange membrane fuel cells.